2015
DOI: 10.1016/j.mehy.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The key role of aquaporin 3 and aquaporin 10 in the pathogenesis of pompholyx

Abstract: Pompholyx remains a chronic skin affliction without a compelling pathophysiological explanation. The disease is characterized by the sudden onset of vesicles exclusively in the palms and soles which generally resolves. However, the disease may progress and the vesicles may expand and fuse; with chronicity there is deep fissuring. Multiple therapeutic approaches are available, but the disease is often resistant to conventional treatments. Currently, oral alitretinoin is used for patients with resistant chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…PPP was defined as multiple creamy‐white pustules on erythematous desquamative plaques (see A) . Pompholyx was defined as acute recurrent vesicular eczema with many deep‐seated pruritic, painful, clear vesicles (see D) . PPP‐PVs with round yellowish areas surrounded by vessels in a linear arrangement were selected by dermoscopy (see B and C) .…”
Section: Methodsmentioning
confidence: 99%
“…PPP was defined as multiple creamy‐white pustules on erythematous desquamative plaques (see A) . Pompholyx was defined as acute recurrent vesicular eczema with many deep‐seated pruritic, painful, clear vesicles (see D) . PPP‐PVs with round yellowish areas surrounded by vessels in a linear arrangement were selected by dermoscopy (see B and C) .…”
Section: Methodsmentioning
confidence: 99%
“…Many reports have described the clinical, histological, immunological and genetic features of PPP patients, but the pathophysiology and etiology remain unclear . Histopathologically, the earliest PPP lesion is a spongiotic vesicle in the lower malpighian layer containing mononuclear cells and some neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have described the clinical, histological, immunological and genetic features of PPP patients, but the pathophysiology and etiology remain unclear. 5,[8][9][10][11] Histopathologically, the earliest PPP lesion is a spongiotic vesicle in the lower malpighian layer containing mononuclear cells and some neutrophils. This progresses to a unilocular, well-delimited pustule within the epidermis that extends upwards to the undersurface of the stratum corneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These form channels which help regulate the flow of water within cells and are found throughout various tissues in the body (Day et al, 2014). In the epidermis aquaporin 3 and 10 play an important role in water balance, and are also involved in the movement of glycerol and urea, both important substances in helping the skin retain moisture (Soler et al, 2015). The early work by Olsson et al (2006) demonstrated altered aquaporin levels in the skin of patients with atopic eczema, particularly of aquaporin 3, and this imbalance is thought to contribute to the rapid and severe formation of dry skin seen in this condition.…”
Section: Normal Skin Barrier Functionmentioning
confidence: 99%